Sources of academic self-efficacy-beliefs: The role of the specificity level of autobiographical memories about academic performance - Vanlede, Marie; Bourgeois, Etienne; Galand, Benoit; Philippot, Pierre (Les Cahiers de Recherche du Girsef, 2009)
The impact on academic self-efficacy beliefs of the specificity at which memories of past academic performance are processed was investigated. Relying on autobiographical memory (AM) theories, it was predicted that, for past academic failures, which represent a threat to self-efficacy beliefs, specific processing would help in maintaining high selfefficacy beliefs compared to general processing. For past academic successes, no difference was expected between the two levels of specificity. An experimental study with 54 psychology students was conducted and results confirmed the main hypothesis. A mediating effect of emotional state on the influence of the specificity of processing past academic performance on self-efficacy beliefs was expected. This mediation could not be evidenced.